X‐ray investigations of GaInN single quantum wells grown by atomic layer epitaxy and metalorganic vapor phase epitaxy. Issue 3 (20th February 2014) - Ju, Guangxu; Kato, Yoshihiro; Honda, Yoshio; Tabuchi, Masao; Takeda, Yoshikazu; Amano, Hiroshi
Abstract: A set of GaN/GaInN single quantum wells (SQWs) were grown on c‐plane GaN/sapphire templates using metal organic vapor phase epitaxy (MOVPE) and atomic layer epitaxy (ALE). The structural information on the interfaces and surfaces was obtained by fitting the experimental X‐ray spectra and was compared between MOVPE and ALE mode. The X‐ray crystal truncation rod (CTR) scattering measurement results showed that the samples grown by ALE had sharper interfaces than those grown by MOVPE. Both the X‐ray reflectivity (XRR) curve‐fitting results and atomic force microscope (AFM) results indicated that the surfaces of the ALE‐grown SQWs were smoother than those of MOVPE‐grown SQWs. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)